2000
DOI: 10.1103/physreva.62.063612
|View full text |Cite
|
Sign up to set email alerts
|

Analytical estimate of the critical velocity for vortex pair creation in trapped Bose condensates

Abstract: We use a modified Thomas-Fermi approximation to estimate analytically the critical velocity for the formation of vortices in harmonically trapped BEC. We compare this analytical estimate to numerical calculations and to recent experiments on trapped alkali condensates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 19 publications
9
50
0
Order By: Relevance
“…Here, the onset of heating is predicted to occur for a relative velocity that equals the sum of the individual sound velocities [9]. In addition to these studies, superfluidity in BECs has been studied in a number of theoretical works based on the Gross-Pitaevskii equation [10][11][12][13]. Further studies were reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the onset of heating is predicted to occur for a relative velocity that equals the sum of the individual sound velocities [9]. In addition to these studies, superfluidity in BECs has been studied in a number of theoretical works based on the Gross-Pitaevskii equation [10][11][12][13]. Further studies were reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…An approach that inserts the calculated energy and momentum of a vortex pair into the Landau criterion, Eq. (5), has yielded a critical velocity of the correct magnitude [30].…”
Section: Stirring a Condensate With A Localized Potentialmentioning
confidence: 99%
“…[10,11] and references therein) employ the Feynman hypothesis and provide a qualitative explanation of the MIT experimental result. In this Letter we point out a simple geometrical effect which is characteristic for elongated cylindrical traps.…”
mentioning
confidence: 99%